Effectiveness of BNT162b2 and CoronaVac vaccinations against mortality and severe complications after SARS-CoV-2 Omicron BA.2 infection: a case–control study. Issue 1 (31st December 2022) - Yan, Vincent Ka Chun; Wan, Eric Yuk Fai; Ye, Xuxiao; Mok, Anna Hoi Ying; Lai, Francisco Tsz Tsun; Chui, Celine Sze Ling; Li, Xue; Wong, Carlos King Ho; Li, Philip Hei; Ma, Tiantian; Qin, Simon; Wong, Vincent Kai Chung; et al.
ABSTRACT: Data regarding protection against mortality and severe complications after Omicron BA.2 infection with CoronaVac and BNT162b2 vaccines remains limited. We conducted a case–control study to evaluate the risk of severe complications and mortality following 1–3 doses of CoronaVac and BNT162b2 using electronic health records database. Cases were adults with their first COVID-19-related mortality or severe complications between 1 January and 31 March 2022, matched with up-to 10 controls by age, sex, index date, and Charlson Comorbidity Index. Vaccine effectiveness against COVID-19-related mortality and severe complications by type and number of doses was estimated using conditional logistic regression adjusted for comorbidities and medications. Vaccine effectiveness (95% CI) against COVID-19-related mortality after two doses of BNT162b2 and CoronaVac were 90.7% (88.6–92.3) and 74.8% (72.5–76.9) in those aged ≥65, 87.6% (81.4–91.8) and 80.7% (72.8–86.3) in those aged 50–64, 86.6% (71.0–93.8) and 82.7% (56.5–93.1) in those aged 18–50. Vaccine effectiveness against severe complications after two doses of BNT162b2 and CoronaVac were 82.1% (74.6–87.3) and 58.9% (50.3–66.1) in those aged ≥65, 83.0% (69.6–90.5) and 67.1% (47.1–79.6) in those aged 50–64, 78.3% (60.8–88.0) and 77.8% (49.6–90.2) in those aged 18–50. Further risk reduction with the third dose was observed especially in those aged ≥65 years, with vaccine effectiveness of 98.0% (96.5–98.9) for BNT162b2 and 95.5% (93.7–96.8) for CoronaVac against mortality, 90.8% (83.4–94.9) and 88.0% (80.8–92.5) against severe complications. Both CoronaVac and BNT162b2 vaccination were effective against COVID-19-related mortality and severe complications amidst the Omicron BA.2 pandemic, and risks decreased further with the third dose.